2018
DOI: 10.1021/acs.langmuir.7b04156
|View full text |Cite
|
Sign up to set email alerts
|

Brownian Translational Dynamics on a Flexible Surface: Nuclear Spin Relaxation of Fluid Membrane Phases

Abstract: A general model for nuclear magnetic resonance (NMR) relaxation studies of fluid bilayer systems is introduced, combining a mesoscopic Brownian dynamics description of the bilayer with atomistic molecular dynamics (MD) simulations. An example is given for dipalmitoylphosphatidylcholine in 2H2O solvent and compared with the experiment. Experimental agreement is within a factor of 2 in the water relaxation rates, based on a postulated model with fixed parameters, which are largely available from the MD simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
(310 reference statements)
0
7
0
Order By: Relevance
“…These models can can incorporate more experimental data at higher field and an other direction is to incorporate information from MD simulations and for-instance resolve the order parameter and population. 8 It is found that approximate tools to compare models can deviate from the complete integral (AIC), or qualitatively follow (BIC), however, the later at large discrepancy at logarithmic scale. The finds suggest that MCMC simulation of Bayesian evidence will play important role in development of NMRD theory, however, method is completely general and can find ample use in other areas of physical chemistry as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These models can can incorporate more experimental data at higher field and an other direction is to incorporate information from MD simulations and for-instance resolve the order parameter and population. 8 It is found that approximate tools to compare models can deviate from the complete integral (AIC), or qualitatively follow (BIC), however, the later at large discrepancy at logarithmic scale. The finds suggest that MCMC simulation of Bayesian evidence will play important role in development of NMRD theory, however, method is completely general and can find ample use in other areas of physical chemistry as well.…”
Section: Discussionmentioning
confidence: 99%
“…3 To obtain more meaningful information from relaxation experiments, relaxation models are utilized to provide details of the mechanisms underlying spin relaxation. 4 Starting from the spinsystem under study relevant mechanism to include may involve dipole-dipole, chemical exchange, paramagnetic and quadrupole contributions, [5][6][7][8][9][10][11][12] as well as chemical shift anisotropy. 13 The challenges in building models involves incorporation of consistent molecular dynamics processes to explain experimental observations and account for spin-dynamics at sufficient accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in the case of testing the structure models 3-5 in a protein framework and in aqueous solution we require a model how the EFG undergoes dynamics due to local bonds and the structure around the Be atoms as well as how the whole protein reorient in solution to allow a computation model of the relaxation rates [39]. Fortunately, modelling of relaxation in complex materials has progressed [37,40], involving cost effective methods for the required quantum chemistry EFGdynamics combined with methods for important slower dynamics. Modelling along this line, combined with collection of experimental data is ongoing to provide both a test of best candidate structural model as well as providing information on the local Be dynamics and the dynamics of the protein as a whole.…”
Section: Be Nmr Linewidth and Relaxationmentioning
confidence: 99%
“…4 Starting from the spinsystem under study relevant mechanism to include may involve dipole-dipole, chemical exchange, paramagnetic and quadrupole contributions. [5][6][7][8][9][10][11][12] The challenges in building models involves incorporation of consistent molecular dynamics processes to explain experimental observations and account for spin-dynamics at sufficient ac- curacy. [13][14][15] Hence, these challenges may come in the form of (i) multiple physical interpretations, (ii) more than one parametrization within a specific physical picture.…”
Section: Introductionmentioning
confidence: 99%